2020
DOI: 10.1002/batt.202000010
|View full text |Cite
|
Sign up to set email alerts
|

Gassing Behavior of High‐Entropy Oxide Anode and Oxyfluoride Cathode Probed Using Differential Electrochemical Mass Spectrometry

Abstract: Multicomponent materials may exhibit favorable Li‐storage properties because of entropy stabilization. While the first examples of high‐entropy oxides and oxyfluorides show good cycling performance, they suffer from various problems. Here, we report on side reactions leading to gas evolution in Li‐ion cells using rock‐salt (Co0.2Cu0.2Mg0.2Ni0.2Zn0.2)O (HEO) or Li(Co0.2Cu0.2Mg0.2Ni0.2Zn0.2)OF (Li(HEO)F). Differential electrochemical mass spectrometry indicates that a robust solid‐electrolyte interphase layer is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 45 publications
(106 reference statements)
7
34
2
Order By: Relevance
“…12 Additionally, using in situ differential electrochemical mass spectrometry (DEMS), the authors revealed that a robust solidelectrolyte interphase (SEI) is formed on the surface of HEO particles, even when using an additive-free electrolyte, further emphasizing the advantage of the proposed entropy-stabilized conversion-type lithium storage mechanism. 79 Notably, the HEO system exhibited a great enhancement in terms of cycling stability when compared to medium-entropy oxide materials (Fig. 9e).…”
Section: The Application Of Heos In the Battery Fieldmentioning
confidence: 96%
See 2 more Smart Citations
“…12 Additionally, using in situ differential electrochemical mass spectrometry (DEMS), the authors revealed that a robust solidelectrolyte interphase (SEI) is formed on the surface of HEO particles, even when using an additive-free electrolyte, further emphasizing the advantage of the proposed entropy-stabilized conversion-type lithium storage mechanism. 79 Notably, the HEO system exhibited a great enhancement in terms of cycling stability when compared to medium-entropy oxide materials (Fig. 9e).…”
Section: The Application Of Heos In the Battery Fieldmentioning
confidence: 96%
“…Entropy stabilization and the occurring interactions between the different incorporated elements endow unique properties of HEMs. In this review, we will focus particularly on the effect that entropy stabilization (and the cocktail effect) has on the applications in electrochemical energy storage, for example, in batteries 12,13,17,18,53,55,69,[76][77][78][79] and supercapacitors. 23,[80][81][82]…”
Section: View Article Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…The high entropy design approach was recently applied to carbides [ 4 , 5 ] borides [ 6 , 7 , 8 ], and oxides [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] for high temperature and battery-related applications. Most of the high entropy compositions that were successfully prepared as single phases are within the 15% limit of atomic radii differences known as a Hume-Rothery [ 19 ] rule to metallurgists and as a Goldschmidt [ 20 ] limit for isomorphic mixtures to mineralogists (the majority of mineral species meet HE definition!…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the recent findings by Bérardan et al on (NiCuZnMgCo) 1−x−y Ga y A x O (with A = Li, Na, K) showed that the charge compensation mechanism when using monovalent elements involves the formation of oxygen vacancies, resulting in a decrease in lattice parameters [18]. Lately, HEOs have been shown to have potential as conversion, intercalation, and insertion materials for application in Liand Na-ion batteries (LIBs and SIBs) [5,13,17,[19][20][21][22]. Nevertheless, the role of Li + in HEO structures (e.g., rock-salt [23] or spinel [24]) and the associated behaviors of the other incorporated elements have not yet been understood.…”
Section: Introductionmentioning
confidence: 99%